Loci controlling lymphocyte production of interferon c after alloantigen stimulation in vitro and their co-localization with genes controlling lymphocyte infiltration of tumors and tumor susceptibility - Lipoldová, Marie; Havelková, Helena; Badalová, Jana; Vojtísková, Jarmila; Quan, Lei; Krulová, Magdaléna; Sohrabi, Yahya; Stassen, Alphons P; Démant, Peter (Cancer immunology and immunotherapy, 2010)
Low infiltration of lymphocytes into cancers is associated with poor prognosis, but the reasons why some patients exhibit a low and others a high infiltration of tumors are unknown. Previously we mapped four loci (Lynf1–Lynf4) controlling lymphocyte infiltration of mouse lung tumors. These loci do not encode any of the molecules that are involved in traffic of lymphocytes. Here we report a genetic relationship between these loci and the control of production of IFNγ in allogeneic mixed lymphocyte cultures (MLC). We found that IFNγ production by lymphocytes of O20/A mice is lower than by lymphocytes of OcB-9/Dem mice (both H2pz) stimulated in MLC by irradiated splenocytes of C57BL/10SnPh (H2b) or BALB/ cHeA (H2d) mice, or by ConA. IFNγ production in MLCs of individual (O20 9 OcB-9)F2mice stimulated by irradiated C57BL/10 splenocytes and genotyped for microsatellite markers revealed four IFNγ-controlling loci (Cypr4-Cypr7), each of which is closely linked with one of the four Lynf loci and with a cluster of susceptibility genes for different tumors. This suggests that inherited differences in certain lymphocyte responses may modify their propensity to infiltrate tumors and their capacity to affect tumor growth.
Keywords: Genetic Loci; test smíšené lymfocytární kultury; Mice, Inbred BALB C; Mice; myši inbrední BALB C; zvířata; genetické lokusy; tumor infiltrující lymfocyty; mužské pohlaví; Isoantigens; isoantigeny; Mice, Mutant Strains; mutantní kmeny myší; Lymphocytes, Tumor-Infiltrating; myši; Interferon-gamma; ženské pohlaví; mapování chromozomů; Animals; Mice, Inbred C57BL; interferon gama; Male; Lymphocyte Culture Test, Mixed; Chromosome Mapping; myši inbrední C57BL; Female